Family Law Enforcement Problems and Islamic Heritage in Thailand - Puteh, Mada O; Jehwae, Phaosan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The Islamic Law on Family and Inheritance of 1946 was enforced only in the four southern provinces of Thailand consisting of Pattani, Narathiwat, Yala and Setun Provinces. Islamic law applies only to the plaintiff, defendant or applicant who submits a request must be Muslim. The problem of law enforcement consists of the lack of clarity in the terms of membership of the Provincial Islamic Committee in the 1997 Law on the Administration of Islamic Organizations. The problem of setting the condition that requires Datok Qadi to be alone in deciding matters of Islamic law. Datok Qadi's decision is absolute and cannot be appealed. The problem of limiting the enforcement of Islamic law can only be enforced in court. Solving the problem in avoiding the legal inconsistency can be done by expanding the enforcement of family and inheritance law outside the court. In addition, there is also a need for legal reform, both the Islamic Law on Family and Inheritance of 1946 and the 1997 Law on Administration of Islamic Organizations which are clearer.Hukum Islam tentang keluarga dan warisan 1946 hanya diberlakukan di empat provinsi selatan Thailand yang terdiri dari Provinsi Pattani, Narathiwat, Yala dan Setun. Hukum Islam hanya berlaku bagi penggugat, tergugat atau pemohon yang mengajukan permohonan harus beragama Islam. Masalah penegakan hukum terdiri dari ketidakjelasan ketentuan keanggotaan Majelis Ulama Provinsi dalam Undang-Undang Tahun 1997 tentang Penyelenggaraan Ormas Islam. Masalah pengaturan kondisi yang mengharuskan Datok Qadi sendirian dalam memutuskan perkara hukum Islam. Keputusan Datok Qadi adalah mutlak dan tidak dapat diganggu gugat. Masalah pembatasan penegakan hukum Islam hanya bisa ditegakkan di pengadilan. Pemecahan masalah dalam menghindari inkonsistensi hukum dapat dilakukan dengan memperluas penegakan hukum keluarga dan waris di luar pengadilan. Selain itu, perlu juga dilakukan pembenahan hukum, baik UU Keluarga dan Kewarisan tahun 1946 maupun UU Administrasi Ormas tahun 1997 yang lebih jelas.Â